Plasma p‐tau217 predicts in vivo brain pathology and cognition in autosomal dominant Alzheimer's disease - Aguillon, David; Langella, Stephanie; Chen, Yinghua; Sanchez, Justin S.; Su, Yi; Vila‐Castelar, Clara; Vasquez, Daniel; Zetterberg, Henrik; Hansson, Oskar; Dage, Jeffrey L.; Janelidze, Shorena; Chen, Kewei; et al. (Alzheimer's & dementia, 2023)
Introduction Plasma‐measured tau phosphorylated at threonine 217 (p‐tau217) is a potential non‐invasive biomarker of Alzheimer's disease (AD). We investigated whether plasma p‐tau217 predicts subsequent cognition and positron emission tomography (PET) markers of pathology in autosomal dominant AD. Methods We analyzed baseline levels of plasma p‐tau217 and its associations with amyloid PET, tau PET, and word list delayed recall measured 7.61 years later in non‐demented age‐ and education‐matched presenilin‐1 E280A carriers (n = 24) and non‐carrier (n = 20) family members. Results Carriers had higher plasma p‐tau217 levels than non‐carriers. Baseline plasma p‐tau217 was associated with subsequent amyloid and tau PET pathology levels and cognitive function. Discussion Our findings suggest that plasma p‐tau217 predicts subsequent brain pathological burden and memory performance in presenilin‐1 E280A carriers. These results provide support for plasma p‐tau217 as a minimally invasive diagnostic and prognostic biomarker for AD, with potential utility in clinical practice and trials. Highlights Non‐demented presenilin‐1 E280A carriers have higher plasma tau phosphorylated at threonine 217 (p‐tau217) than do age‐matched non‐carriers. Higher baseline p‐tau217 is associated with greater future amyloid positron emission tomography (PET) pathology burden. Higher baseline p‐tau217 is associated with greater future tau PET pathology burden. Higher baseline p‐tau217 is associated with worse future memory performance.